The Representation of Indonesian National Identity in English Textbook - Ella Masita (Indonesian Research Journal in Education |IRJE|, 2021)
This article interrogates the conceptualization of Indonesian national identity from the point of view of the Indonesian government. The data were taken from a mandatory English textbook for Grade XI. Through the lens of Representation theory, this research explores the key issues within the textbook. In analyzing the data, a multimodal discourse analysis is utilized, specifically through the verbal analysis and visual analysis of the texts within the textbook. The results of analysis reveal that there are four themes namely: spirituality and morality, personal attribute, nationalism, and knowledge and scientific attitude. However, the research results indicate the inclusion of selected values and norms of personal attributes, the unbalanced portion of the themes within the textbook and minimal representation of the knowledge development, specifically in regards to the development of English skills. Apart from that, it is realized that textbook is only one part of elements in English teaching process. Therefore, further studies with a broader scope of investigation are required to achieve more comprehensive information about how Indonesian national identity in conceptualized in English teaching.